Flexing di Instagram: Antara Narsisisme dan Benefit - Keyrina Adinda (Emik, 2023)
Instagram is a popular photo and video-based social media platform in Indonesia. At first, the photos and videos uploaded were simple. But now, Instagram users are starting to pay attention to quality; they are even willing to spend money and time to make an ideal upload. An ideal post, such as showing happiness or one that is exclusive in terms of both financial and personal achievement. Nowadays, this behavior has became known as flexing. Flexing then mushroomed not only among upper and middle class, but also lower class. This article explores this flexing behavior. This study was conducted on Instagram as this social media platform that first popularized flexing, and there are still many flexing actors on Instagram. This study was conducted between September and December 2022, involving 13 informants, who vary according to sex (7 women and 6 men), age (between 19 and 24 years), and status (six flexing agents, four followers, and three flexing agents as well as followers). Interview and observation were combined as data collection methods. While the former was carried out through face-to-face interview and online interview using Zoom application and Instagram direct messages; the latter was conducted by observing their Instagram accounts. The study indicates that even though flexing, by definition is related to showing off wealth, the research finding indicates that it also includes one’s achievement (i.e. one’s performance, ideal body, expertise). Those who do flexing suggest that Instagram is one’s personal property and they have the right to upload whatever they want. Based on this, the reasons for doing flexing vary, ranging from self-appreciation and appreciated by other, to archive something they have or achieve, and personal branding. Flexing has both positive and negative impacts on the person doing it and on other people. The positive impacts on flexing actors are self-motivation, making new friends, and opening up job opportunities. The positive impacts on others are motivation, and sources of information. Meanwhile, The negative impacts of Flexing for actors are that they become more wasteful and spend a lot of time. The negative impacts on others, it creates a feeling of insecurity and pressure because they compare themselves with others.